Effect of ethephon and planting density on lodged plant percentage and crop yield in maize (Zea mays L.) - Chandiposha, Misheck; Chivende, Fanuel (Academic Journals, 2016)
Increasing maize production is vital in many developing countries. One way of increasing production is through adoption of high planting densities. However, high planting densities are associated with intraspecific competition between plants for resources like nutrients, water and sunlight, as a result weak stalks develops which are susceptible to lodging. The challenge of lodging in high planting densities can be reduced by ethephon (2-chloroethylphosphonic acid). A 3 x 2 factorial experiment in randomised complete block design was carried out at New Donnington Farm, Zimbabwe in the 2011/12 rainy season to study the effects of ethephon rates and planting densities on maize. Ethephon rate had the following levels 0 l/ha (control), 0.56 l/ha and 0.84 l/ha while the density consisted of 53,333 and 80,000 plants/ha. Ethephon rate significantly (p˂0.05) reduced the plant height of maize as compared to the control plants across different levels of planting densities. Also a significant increase (p˂0.05) in internode diameter in the treated stands over the control plants across different levels of planting densities was recorded. Ethephon treatment significantly reduced (p˂0.05) the percentage of lodged plants from 6.54 (control) to 4.34 and 2% for medium and high rate, respectively. Grain yield increased significantly in response to increased rates of ethephon at high planting density by 28.5 and 29.1 tons/ha for medium and high rate, respectively.